2014
DOI: 10.1016/j.cell.2014.04.017
|View full text |Cite|
|
Sign up to set email alerts
|

Programming and Inheritance of Parental DNA Methylomes in Mammals

Abstract: The reprogramming of parental methylomes is essential for embryonic development. In mammals, paternal 5-methylcytosines (5mCs) have been proposed to be actively converted to oxidized bases. These paternal oxidized bases and maternal 5mCs are believed to be passively diluted by cell divisions. By generating single-base resolution, allele-specific DNA methylomes from mouse gametes, early embryos and primordial germ cell (PGC), as well as single-base resolution maps of oxidized cytosine bases for early embryos, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
431
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 472 publications
(490 citation statements)
references
References 51 publications
39
431
2
5
Order By: Relevance
“…To examine the patterns of DNA methylation, we study data from mouse early embryo (GSM1386021), 17 which includes 5mC reads of each CpG sites from different stages of mouse embryo from sperm/oocyte to E13.5. In mouse genome, the distances between adjacent CpG sites range from two to a few thousand bp.…”
Section: Pearson Correlations Between Cpg Site Methylationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the patterns of DNA methylation, we study data from mouse early embryo (GSM1386021), 17 which includes 5mC reads of each CpG sites from different stages of mouse embryo from sperm/oocyte to E13.5. In mouse genome, the distances between adjacent CpG sites range from two to a few thousand bp.…”
Section: Pearson Correlations Between Cpg Site Methylationsmentioning
confidence: 99%
“…During mouse gametes and early embryos, most functional genomic elements undergo significant demethylation, except CpG islands (CGIs) and 5 untranslated regions (UTRs) whose methylation levels are already very low in gametes. 17 In zebrafish early embryos, the oocyte methylome is gradually discarded after 16-cell stage, and then progressively reprogrammed to a pattern similar to that of the sperm methylome. 10 DNA methylation patterns of human hematopoietic stem cells (HSCs) from four different sources show different profiles, and DNA methylation dynamics of myeloid-lymphoid lineage choice displays an asymmetric pattern.…”
mentioning
confidence: 99%
“…However, a number of studies have demonstrated that replicationdependent and -independent (through TET3-mediated oxidation of 5mC to 5hmC) demethylation mechanisms coexist in both male and female pronuclei of mouse zygotes (Salvaing et al 2012, Guo et al 2014a, Shen et al 2014, Wang et al 2014. In the human zygotes at the pronuclear stage, hydroxymethylation of both male and female pronuclei with lower immunofluorescent signal in female pronuclei has been reported by Guo et al (2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of TET-mediated oxidation of 5mC suggested that the oxidation product -5-hydroxymethylcytosine (5hmC) -is an intermediate in the active DNA demethylation (Tahiliani et al 2009, Ito et al 2010. The involvement of 5hmC in the DNA methylation reprogramming thus far has been demonstrated in mouse, rabbit, bovine, and porcine preimplantation embryos (Inoue & Zhang 2011, Iqbal et al 2011, Wossidlo et al 2011, Salvaing et al 2012, Zhang et al 2012, Cao et al 2014, Wang et al 2014. Relevant data in human have not been obtained yet.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the decline in 5mC in the paternally derived genome is accompanied by a prominent increase in 5hmC and less prominent increases in 5fC and 5caC (Gu et al 2011, Inoue & Zhang 2011, Iqbal et al 2011, Wossidlo et al 2011, Zhu et al 2017. TET3 is also present in the maternal pronucleus, but 5mC is largely protected from active demethylation (Guo et al 2014, Peat et al 2014, Shen et al 2014, Wang et al 2014, Zhu et al 2017. The PGC7 (also called STELLA or DPPA3) protein, which is genomically recruited through H3K9me2, is a candidate to mediate protection of 5mC in the maternal genome against active demethylation (Nakamura et al 2007, 2012, Wossidlo et al 2011, Bian & Yu 2014.…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%